1979
DOI: 10.1002/ijc.2910240614
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of an ascitic rat hepatoma with cord factor (trehalose‐6, 6′‐dimycolate) and synthetic analogues

Abstract: The ability of cord factor (trehalose-6, 6'-dimycolate) and a range of shorter carbon chain fatty acid trehalose diesters to suppress growth of an ascitic rat hepatoma has been examined and compared with that of whole, living BCG organisms. Aqueous suspensions of BCG, and cord factor in 0.4% arachis oil:Triton emulsion, injected intraperitoneally, retarded growth of up to 10(5) ascites tumour cells. Trehalose-6, 6'-dibehenate was also tumour-suppressive, but only against lower challenge inocula (10(4) cells). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Since cancer research in the early 1970s indicated a possible correlation between some infections and tumor suppression (8), much focus has been put on the identification of single components responsible for this effect. These studies led to the identification of the mycobacterial cell wall component trehalose dimycolate (TDM) as a tumor suppressive molecule (49). In later years, the immunomodulating effect of this highly active molecule has been determined and it has been found to activate macrophages and to stimulate a broad panel of cytokines, including IL-12, tumor necrosis factor alpha, and IFN-␥, thus driving a Th1 response (39,60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since cancer research in the early 1970s indicated a possible correlation between some infections and tumor suppression (8), much focus has been put on the identification of single components responsible for this effect. These studies led to the identification of the mycobacterial cell wall component trehalose dimycolate (TDM) as a tumor suppressive molecule (49). In later years, the immunomodulating effect of this highly active molecule has been determined and it has been found to activate macrophages and to stimulate a broad panel of cytokines, including IL-12, tumor necrosis factor alpha, and IFN-␥, thus driving a Th1 response (39,60).…”
Section: Discussionmentioning
confidence: 99%
“…This immunostimulatory effect has been utilized in several adjuvant formulations (36,43), but indications are that TDM is likely to be too toxic for use in prophylactic vaccines (6,29). Since the synthetically produced TDB, which has shorter, less saturated carbon chain fatty acids, is less toxic than TDM but has retained much of the bioactivity of the native form (46,49), TDB was tested as a novel Th1-promoting adjuvant component in the present study. Certainly the potent IFN-␥-promoting qualities of this immunomodulator when tested in vivo suggest that TDB, like native TDM, is able to stimulate APCs to synthesize and secrete IFN-␥-promoting molecules such as IL-12 and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, immunization with TDM did not elicit an IFN-c response to TDB, thus showing specificity of response. Although not antigenic, other investigators have shown that the analogue TDB retains partial immunogenic effects similar to those of TDM (Pimm et al, 1979). While BCG vaccine experiments indicate that TDB can be an effective adjuvant when mixed with dimethyl dioctadecyl ammonium bromide, it has not been proven to work alone, and appears to elicit responses to the incorporated formulated protein antigens (Holten-Andersen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic mycobacterial lipid in adjuvant formulations has also previously been exploited successfully, e.g., TDB, which contains shorter, less saturated acid chains and is less reactogenic than the native compound TDM (21,22). However, as it has retained much of the biological activity, it is highly effective in adjuvant formulations and has shown promising results in a range of animal models, including TB and chlamydia (23,24).…”
Section: Discussionmentioning
confidence: 99%